Interaction family System associated with lower self-esteem in moral abandonment or prostitution - Ferreira Rocha, Alaírdes María (2003)
This is a descriptive study about 160 youngsters from Lima: 80 that are involved in moral abandonment or prostitution and 80 of similar characteristics but not involved in prostitution. They were applied two inventories: Family adaptability and cohesion evaluation (FACES - III) and Self-esteem of Coopersmith. The results show significant statistics differences between the means in cohesion, family adaptability and Self-esteem when the groups of youngsters in moral abandonment and prostitution were compared with the control group. Besides, there is a high relationship between the types of family (Balance, mean rank and extreme) and the levels of self-esteem with the groups of youngsters in moral danger or prostitution and those who are not in this condition.